2023
DOI: 10.3390/app13158853
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Effect of the Films Coated with the Layers Based on Uncaria tomentosa and Formitopsis betulina Extracts and ZnO Nanoparticles and Their Influence on the Secondary Shelf-Life of Sliced Cooked Ham

Magdalena Ordon,
Weronika Burdajewicz,
Józef Sternal
et al.

Abstract: Microbial surface contamination of the cooked ham sliced by shop assistants has an influence on its potential secondary shelf-life. Active packaging may be the solution. The first goal of the work was to obtain coatings based on Formitopsis betulina and Uncaria tomentosa extracts (separately), with the addition of nanoparticles of ZnO (as a synergetic agent to increase plant extracts’ antimicrobial effectiveness), that could be active against selected bacterial strains. Another aim of the work was to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The authors' [10] findings led to the theory that the introduction of the ZnO nanoparticles (separately) into the F. betulina or into the Verbasculum L. or the U. tomentosa extracts may cause a synergistic effect between two active agents. Other experiments carried out by the authors [26] also confirmed these assumptions. The coatings including F. betulina or U. tomentosa extracts with zinc oxide nanoparticles as active agents, which were found to be highly active against Staphylococcus aureus, Escherichia coli and B. atrophaeus cells.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…The authors' [10] findings led to the theory that the introduction of the ZnO nanoparticles (separately) into the F. betulina or into the Verbasculum L. or the U. tomentosa extracts may cause a synergistic effect between two active agents. Other experiments carried out by the authors [26] also confirmed these assumptions. The coatings including F. betulina or U. tomentosa extracts with zinc oxide nanoparticles as active agents, which were found to be highly active against Staphylococcus aureus, Escherichia coli and B. atrophaeus cells.…”
Section: Introductionsupporting
confidence: 62%
“…It was also concluded in a previous work that a Ut active coating was able to display a greater effect on the growth of bacteria than an Fb coating, though for a shorter time [26]. Due to their antibacterial effectiveness, they were also confirmed as retaining the quality and freshness of slices of cooked ham during secondary shelf-life (48 h) [26]. This is why the ZnVL and ZnFb active layers (more effective than ZnUt layer), which exhibit antibacterial and antifungal properties, were selected to preserve the strawberries during these storage tests.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…First, low-cost commercial ZnO NPs serve as the active core of nanocomposite against Psa . 50–54 In addition, the incorporation of PDA ensures uniform deposition of the metal enzyme-like active sites on the surface, enhancing biocompatibility. 55 The nanocomposites, with excellent CAT-like activity, exhibit K m and V ma x values superior to that of most reported nanozymes, efficiently converting H 2 O 2 into O 2 .…”
Section: Introductionmentioning
confidence: 99%